Proceedings of the 33rd Annual ACM Conference on Human Factors in Computing Systems 2015
DOI: 10.1145/2702123.2702412
|View full text |Cite
|
Sign up to set email alerts
|

From User-Centered to Adoption-Centered Design

Abstract: As we increasingly strive for scientific rigor and generalizability in HCI research, should we entertain any hope that by doing good science, our discoveries will eventually be more transferrable to industry? We present an in-depth case study of how an HCI research innovation goes through the process of transitioning from a university project to a revenue-generating startup financed by venture capital. The innovation is a novel contextual help system for the Web, and we reflect on the different methods used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…For example, Pinelle and Gutwin's 1998 questions regarding "How do we evaluate" resonate with advocates for "adoption-centred design" [4] that can aid in translating HCI research to commercial products. Similarly, the eld continues to struggle with foundational aspects of CSCW, such as Grudin's Eight Challenges for Groupware [13], and their application to new technologies such as public wall displays [5] and social computing [3].…”
Section: How Do We Synthesize Results?mentioning
confidence: 99%
“…For example, Pinelle and Gutwin's 1998 questions regarding "How do we evaluate" resonate with advocates for "adoption-centred design" [4] that can aid in translating HCI research to commercial products. Similarly, the eld continues to struggle with foundational aspects of CSCW, such as Grudin's Eight Challenges for Groupware [13], and their application to new technologies such as public wall displays [5] and social computing [3].…”
Section: How Do We Synthesize Results?mentioning
confidence: 99%
“…Buur et al observed, doing user studies of forklift operators, that the skilled operators perform many operations in parallel, as well as, tasks far beyond the everyday notion of 'lifting', 'carrying' and 'dropping' a load [36]. The knowledge must therefore be based system use and adoption "in the wild", thus giving a true understanding of use to complement laboratory tests and prior assumptions [37,38]. Benyon notes that designers need to understand the people who will use their systems and products.…”
Section: Discussionmentioning
confidence: 99%
“…Others have identified various problems that can arise when scaling up research projects [11,18,43]. For example, Chilana, Ko, and Wobbrock [18] discuss the challenges of moving from a research project to a commercial product, noting how there are multiple stakeholders that need to be taken into account aside from users, including business customers, administrators, financers and regulators.…”
Section: Scaling Up Hci Researchmentioning
confidence: 99%
“…Others have identified various problems that can arise when scaling up research projects [11,18,43]. For example, Chilana, Ko, and Wobbrock [18] discuss the challenges of moving from a research project to a commercial product, noting how there are multiple stakeholders that need to be taken into account aside from users, including business customers, administrators, financers and regulators. Blumenfeld et al [11] note, too, the unforeseen challenges they faced when trying to scale up a technology that they had developed for a school setting, including dealing with school legislation, limited resources, and organizational culture.…”
Section: Scaling Up Hci Researchmentioning
confidence: 99%